Injury to the axillary artery and brachial plexus caused by a closed floating shoulder injury: A case report - Chen, Yu-Chun (World J Clin Cases, 2018)
BACKGROUND: A floating shoulder may be associated with catastrophic neurovascular injury and requires a multidisciplinary approach for its management. To maximize the likelihood of good patient outcomes, this unique injury pattern should be recognized in patients as early as possible. This can be difficult to achieve, however, as there are currently few reports of floating shoulder in the literature, meaning that associated neurovascular injuries may be overlooked. CASE SUMMARY: We present here a rare case of floating shoulder with axillary artery injury in a 34-year-old woman. The patient complained of pain and numbness of her left upper limb after losing control of her motorcycle on a highway and falling from the vehicle 2 h ago. No blood pressure reading could be obtained from her left upper limb and no blood oxygen readings could be obtained from any of her left fingers. Computed tomography angiography and duplex ultrasonography revealed interruption of blood flow through the axillary artery, with distal flow being maintained through collateral arteries. The clinical diagnosis including fracture of the left proximal humerus, the left clavicle, and the left scapula, left axillary artery rupture, and left brachial plexus injury. We successfully performed open reduction and internal fixation of the fracture and vascular repair. The patient showed satisfactory recovery that was observed during 4-mo follow-up. CONCLUSION: Emergency surgery can be an effective therapeutic option for the closed floating shoulder with catastrophic axillary artery injury.